IBN RUSHD’S INTELLECTUAL STRATEGIES ON ISLAMIC THEOLOGY - Hamid Fahmy Zarkasyi; Amal Fathullah Zarkasyi; Tonny Ilham Prayogo; Rahmat Ardi Nur Rifa Da’i (Universitas Islam Negeri Ar-Raniry, 2020)
Islamic theology as axiology that advocates various social inequalities both social and religious aspects. Although it is recognized that Ibn Rushd had the capacity as the greatest Muslim philosopher who was influential not only in the Islamic world but in the West. However, another fact Ibn Rushd was also an Islamic theologian based on philosophical and jurisprudential views. Both of these sources influenced Ibn Rushd's theology which was more rational but did not lead liberal because it was following his jurisprudence. This simple research is a type of library research, using theological approach. In this article, the writer wishes to present the analysis of Ibn Rushd on the views of theology, Ibn Rushd wa not only theologian but also a philosopher and jurist of Islam. This was interesting to be discussed; first, whether Ibn Rushd’s theology was different from other figures of theologians. Second, whether his philosophical and jurisprudential view affected his theology thought. The result of this writing showed that Ibn Rushd had unique strategies on Islamic theology, so the two strategies are Dalil al-‘Inayah and Dalil al-Ikhtira’. In this strategies, showed that Ibn Rushd had unique theology thought which his philosophical and juristprudential view affected his theology so that his theology was more rational but it was not too liberal. So in this article. Showed that Ibn Rushd had application are explained three important thoughts of Ibn Rusyd relating to the themes of Kalam namely; The oneness of God, the attributes of God and the matter of monotheism